Decision Making of Charity Fund Allocation: Evidence from Hong Kong - FONG, Chun Cheong Steve (Financial Risk and Management Reviews, 2020)
This article aims to study the financial decision-making mechanism by charity funding organizations in Hong Kong using case study approach. As charitable resources are limited, social return on investment (SROI) has become a commonly accepted approach by charity foundation trustees. Lo Kwee Seong Foundation in Hong Kong is one family supported charity foundation to exercise such kind of charity funding decision-making mechanism. Funding principles and project selection guidelines were first illustrated. Professional screening and selection processes were also detailed. Then three approved funding proposals and another three rejected funding proposals were illustrated to demonstrate the considerations when the Foundation handled the funding decision process. These cases provided evidences to explain practical issues of how SROI contributed to the charity fund allocation decision. Impacts of other non-financial, especially behavioral decision-making concerns were illustrated. Limitations of the case study approach were also discussed to reflect the practical concerns in company finance data collection.